Central Asia in the Administrative System of the Achaemanian Rule (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The peoples of Central Asia were part of the Achaemenid state for more than 200 years, and during this time (539-329 BC) the ruling order and titles (status, position) characteristic of the ancient Persian Empire prevailed in the region.